Economic interdependence and post-coup democratization. Issue 5 (29th July 2017) - Chacha, Mwita; Powell, Jonathan
ABSTRACT: Despite being traditionally seen as the largest threat to democratization, coups have recently been argued to provide a window of opportunity for a democratic transition. Central to post-coup democratization is the belief that the international community can exert sufficient leverage to coerce coup-born governments to allow a transition to civilian rule. We contribute to this young body of work by theorizing that less coercive aspects of transnational economics can prompt coup-born governments to voluntarily transition to civilian rule. In short, we argue that coups in states that are more closely tied to the international economy through trade dependence, and are more vulnerable to loss of investor confidence due to reliance on high contract intensiveness, will see coup-born governments attempt to legitimize a new government and to restore confidence in the rule of law by swiftly stepping down. A cross-national assessment of over 200 coups from 1950 to 2010 provides strong support for the argument, as trade dependence and contract intensive money are far stronger determinants of post-coup democratization than other factors commonly associated with democratization.